Integration between art and science : an art appreciation of Nyawa Light Exhibition / May Tasneem Nor Adzaman, Mumtaz Mokhtar and Alif Haiqal Musa - May Tasneem, Nor Adzaman; Mumtaz, Mokhtar; Alif Haiqal, Musa (Universiti Teknologi MARA, Perak, 2020)
This study aspires to inform that collaborative artwork between art and science play crucial role in order to bridge the gap between art and science field. This research is to actually meet the objective such as study the contextual analysis based on the selected artwork from the Nyawa's light exhibition at the same time analyse the formalistic artwork and also interpret the aesthetical content of the selected artwork from Nyawa's light exhibition. In the present paper, the research method is described by qualitative study through two different methods which are through interview with three different artists from three different categories and through close observation. The findings were that collaborative artwork between art and science exposed the idea of understanding between both fields. Regarding to the statement the research creates a communication platform through artistic visualization on scientific theory that lead to new media exploration based on new ideology and invention.